IMPLEMENTASI KOMUNIKASI EFEKTIF TERHADAP KELENGKAPAN GENERAL CONSENT RAWAT INAP DI UNIT REKAM MEDIS RUMAH SAKIT KRISTEN MOJOWARNO JOMBANG PROVINSI JAWA TIMUR - saraswati satya kusumaningrum (ITKM WIDYA CIPTA HUSADA, 2022)
General consent is a statement of consent to receive health services obtained from a person during the intake process at the initial visit, before receiving health services, this thesis is the result of a study that describes how much influence the officer's communication regarding general consent has on patients which resulted in many things found in September 2021, there were 20 general consents found in September 2021. incomplete hospitalizations of 67% of the 30 patients were found in the type of payment, the signature of the officer, and the name of the officer 's light